2004
DOI: 10.1128/aac.48.9.3552-3555.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nelfinavir Resistance Mutations on In Vitro Phenotype, Fitness, and Replication Capacity of Human Immunodeficiency Virus Type 1 with Subtype B and C Proteases

Abstract: Human immunodeficiency virus type 1 subtype B and C proteases were manipulated to contain 90M, 88D, or 89L, and their in vitro biological properties were studied. We showed that D30N has significantly more impact in subtype C than in subtype B counterparts, accounting for the reported low prevalence of this mutation in patients failing nelfinavir-based regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 19 publications
(13 reference statements)
8
43
0
Order By: Relevance
“…Extensive differences between the subtypes were found for the minor protease substitutions, which do not impair drug susceptibility but may affect the genetic pathway of resistance once the virus generates a relevant major substitution (47,83,106). This finding implies that a faster emergence of drug resistance to a particular protease inhibitor could be expected in some non-B subtypes.…”
Section: Correlation Between Hiv-1 Genetic Diversity and Drug Resistancementioning
confidence: 78%
“…Extensive differences between the subtypes were found for the minor protease substitutions, which do not impair drug susceptibility but may affect the genetic pathway of resistance once the virus generates a relevant major substitution (47,83,106). This finding implies that a faster emergence of drug resistance to a particular protease inhibitor could be expected in some non-B subtypes.…”
Section: Correlation Between Hiv-1 Genetic Diversity and Drug Resistancementioning
confidence: 78%
“…The L90M mutation, that confers resistance to NFV and SQV, is rare in subtype F but common in subtype B in patients from Brazil (Calazans et al, 2005). D30N has a stronger negative impact in the replicative capacity of C subtype than in B subtype (Gonzalez et al, 2004), which could explain the low frequency of this mutation observed in subtype C infected individuals failing NFVcontaining regimens. A recent study in Portuguese patients, reported that mutation I54V/L was selected by NFV in subtype G isolates, a mutation not previously described for this drug in subtype B (Santos et al, 2009).…”
Section: Impact Of Hiv-1 Diversity In Drug Resistancementioning
confidence: 94%
“…For example, D30N is observed much less frequently relative to L90M in subtype C isolates compared with subtype B. Interestingly, D30N appears to have a greater adverse impact on fitness in a subtype C reverse transcriptase backbone than in a subtype B backbone, suggesting that reduced fitness makes the selection of D30N less likely in a subtype C background (70,76).…”
Section: Mutational Interactions That Affect Fitness Intragenic Intermentioning
confidence: 98%